Russian civilizational project facing digital capitalism - N. B. Afanasov (Омский научный вестник: Серия "Общество. История. Современность")
The article offers a point of view on the Russian civilizational project from the perspective of comparing the national features of Russia’s development and the global expansion of digital capitalism. The author places the Russian civilizational project in the context of processes that will inevitably have — and already have — the impact on modern Russian society and economy. Digital capitalism is as relevant a phenomenon for Russia as it is for any other modern country. The global context and modernization are inextricably linked. But when we talk about modernization, even in the most general way, we cannot exclude the national peculiarities of its implementation, which say a lot about the country itself and its culture. In the context of the Russian civilizational project, the main issue will be to understand why, unlike other modernizing waves, digital capitalism has so quickly become embedded in the space of Russian economic life and Russian culture. What exactly in our culture created such a fertile ground for the phenomenon? It is likely that the absence of established capitalist institutions played a role in the introduction of digital practices. But, as in every culture, there is also something special about Russian culture that accelerates the integration of society into the reality of digital capitalism